Spectra of transverse excitations in liquid glass-forming metallic alloy Mg₇₀Zn₃₀: temperature dependence - Bryk, T.; Mryglod, I. (Condensed Matter Physics, 1999)
The temperature dependence of the dispersion and damping coefficients
of transverse excitations in metallic alloy Mg₇₀Zn₃₀ at the number density n= 0.0435 A⁻³ is studied using the method of generalized collective
modes. The spectra of generalized transverse modes have been obtained
within the four-variable approximation for three temperatures 1210 K, 833 K
and 713 K. It is shown that the propagating gap which characterizes the
crossover between hydrodynamic fluid-like and viscoelastic solid-like behaviour reduces when the temperature decreases. The generalized k-dependent shear viscosity n(k) calculated within the same approximation increases rapidly at k = 0 and its shape becomes more narrow by transition
from a well-de ned liquid state to an undercooled one. Методом узагальнених колективних мод досліджується температурна залежність дисперсії та коефіцієнтів згасання поперечних збуджень у металічному сплаві Mg₇₀Zn₃₀ з густиною частинок n= 0.0435 A⁻³. Спектри поперечних збуджень розраховані у чотиримодовому наближенні для трьох значень температури: 1210 K, 833 K і
713 K. Показано, що розмір пропагаторної щілини, яка визначає перехід від гідродинамічної рідинної поведінки до поведінки властивої
пружному твердотільному середовищу, зменшується при пониженні
температури. Проведено розрахунок узагальненої (залежної від модуля хвильового вектора k) зсувної в’язкості n(k) і показано, що її величина при k = 0
швидко зростає, а функція n(k) стає більш вузькою
при переході від добре визначеного рідкого стану до стану переохолодженої рідини.